Design and Development of a Melon Shelling Machine - Ojo I. ENOCK; Ibrahim A. SAIDU; Ibrahim SULAIMAN; Oluwafeyisikemi. Y. ENOC (FUDMA Journal of Engineering and Technology, 2025)
A melon shelling machine was designed and fabricated. The machine was designed to handle a capacity of 50 kg/hr of melons. This paper presents the design and fabrication of a melon shelling machine designed to mechanize the seed extraction process from melons. The machine was conceptualized to address the inefficiencies of manual shelling, including high labour costs and seed wastage. The power requirement was determined to be 0.6 kW and a 35 mm shaft was selected. Key features of the machine include an intake hopper, shelling unit, and a separation system, all powered by an electric motor. Fabrication used cost-effective, easily available materials, emphasizing robustness and maintenance ease.